The Holocaust, 80 years on [videorecording (DVD)] - Schama, Simon; Schama, Simon (WNET Group, PBS, BBC, 2025)
In the year marking the 80th anniversary of the liberation of the last concentration camps, renowned historian Sir Simon Schama confronts the history of the Holocaust as not just a Nazi obsession, but as a European-wide crime. In the most personal and unflinching film of his career, Simon visits mass killing sites in Lithuania, the home of his mother₂s family. He travels to the Netherlands, a nation famed for its long history of tolerance and where he lived and worked as a young historian, to answer the question of why fewer Jews survived here than in any other Western occupied country. And despite a lifetime dedicated to documenting Jewish history, this film also captures the emotional toll of Simon's first ever visit to Auschwitz-Birkenau.